2001
DOI: 10.1006/ijhc.2001.0458
|View full text |Cite
|
Sign up to set email alerts
|

The influence of reading speed and line length on the effectiveness of reading from screen

Abstract: With such a large volume of material accessible from the World Wide Web, there is an urgent need to increase our knowledge of factors in#uencing reading from screen. We investigate the e!ects of two reading speeds (normal and fast) and di!erent line lengths on comprehension, reading rate and scrolling patterns. Scrolling patterns are de"ned as the way in which readers proceed through the text, pausing and scrolling. Comprehension and reading rate are also examined in relation to scrolling patterns to attempt t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
2
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(80 citation statements)
references
References 26 publications
5
64
2
4
Order By: Relevance
“…However, Dyson and Haselgrove (2001) found that a medium line length (55 characters per line) appears to support effective reading at normal and fast speeds as well as producing the highest level of reading comprehension. On the other hand, Chen and Chien (2005) pointed out that the writing system of English and Chinese is essentially different.…”
Section: Questionnaire Surveymentioning
confidence: 91%
“…However, Dyson and Haselgrove (2001) found that a medium line length (55 characters per line) appears to support effective reading at normal and fast speeds as well as producing the highest level of reading comprehension. On the other hand, Chen and Chien (2005) pointed out that the writing system of English and Chinese is essentially different.…”
Section: Questionnaire Surveymentioning
confidence: 91%
“…The intuition is that the "return sweep" from the end of one line to the beginning of the next is more difficult in wide paragraphs because of the longer eye movement required by the reader. More recently, however, researchers in ergonomics and human factors have re-visited the issue with reading from computer screens [1,3,4,5,14]. In contrast with print studies, reading speed on computer screens favored longer lines (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…First, the similar readability was found irrespective of the line length as far as the line length does not exceed a certain limit [2]. Second, the optimum line length that corresponds to optimum readability differed depending on researchers and experiments [2,3].…”
Section: Introductionmentioning
confidence: 73%
“…With regard to the computer screen environment, the average text width preferred by the subjects on the computer screen was found to be around 100mm [2,3]. An experiment measuring the number of characters showed similar results of 55 characters per line (cpl) [2] and 55-70 cpl [3]. Based on these studies, web designs with a specific fixed text width were recommended [3,4].…”
Section: Introductionmentioning
confidence: 98%